(untitled) (Research, Society and Development, 2020)
Objective: To apply an experience in the implementation of educational actions on coronavirus control measures, focusing on the proper use of Personal Protective Equipment. Methodology: this is an experience report by a group of nurse professors from the Federal University of Southern Brazil, who performs in-service education actions for professionals working in primary health care, to deal with coronary diseases. As actions carried out from March to April 2020, organized in two stages: the first included a search for reliable literature to support a proposal, construction of material with an activity plan and preparation of a video class. Afterwards, face-to-face meetings were held with professionals involved, based on the Paulo Freire method. These meetings were attended by professionals who work in five basic health units managed by the University. After being carried out with a group of multipliers composed of professionals from the municipal health department. Results: In the face-to-face stage, 98 professionals were trained. At the time of training, professionals can expand the link with the documents, export and answer questions and practice, correctly, the use of personal protective equipment or an aid in the control of coronavirus. Conclusion: how health education actions provided scientific knowledge in care practice, expanding professional qualification and the safety of professionals involved in combating a pandemic.